Examining the Mediating Role of Students’ Campus Life Satisfaction on the Relationship between Quality of Campus Life and Loyalty - Mahadzirah, Mohamad; Morliyati, Mohammad; Nur Izzati, Ab Ghani (2015)
This paper discusses the impact of several aspects of quality of campus life, such as academic, facilities and services, and social, on students’ loyalty to the university. This study examines students’ satisfaction with campus life as the mediating variable in the relationship between the two constructs. Using a proposed theoretical model, empirical examination of the major constructs and their underlying dimensions were measured and tested employing structural equation modelling. The selection of the respondents was executed in two stages. The first stage involved stratified sampling and the second stage adopted simple random sampling. Questionnaires were distributed to respondents at the end of their lectures. The survey was conducted among students attending a public university in Malaysia. After data cleaning process, a total of 1,348 dataset, involving students from different years of study, were subjected to further analysis. The findings of the study provide insightful information pertaining to which aspects of campus life that required enhancement to improve students’ campus life satisfaction. The results show that social aspect of campus life requires improvement more than the other two aspects of quality of campus life. This study indicates that student campus life satisfaction mediates the relationship between quality of campus life and loyalty. According to survey results it is also suggested that university administrators should focus on improving facilities and services, in order to improve students’ campus life satisfaction, which eventually leads to students’ loyalty.